The impact of social intelligence on academic achievement - Bal, Pervin; Yıldırım, Osman; Yıldırım, Halil (Int Scientific Conference SGEM, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2008)
In the research, The Resilience Scale for Adults (RSA-scale) proposed by Hjemdal, Friborg, Martinussen, and Rosenvinge was used to assess students' social intelligence. RSA-scale is consisted of 45 items including live dimensions: (1) personal competence, (2) social competence, (3) family coherence, (4) social support, and (5) personal structure. The internal consistency (Chronbach's alpha) of all the dimensions is satisfactory high. The inventory was completed by the students twice, separated by a two-month interval in order to minimize the translation errors. 452 students at file Turkish University of Vocational Studies participated in this research. The total sample was used for confirmative analyses of the factor structure of the RSA and correlations.
Keywords: Social Intelligence; Social Preference; Academic Achievement